RECONSTRUCTING SOCIAL PIETY: OVERCOMING THE HYPER-INDEPENDENCE OF GENERATION Z PERSPECTIVE OF AL-QUR'AN SURAH AL-MA'UN - Muh. Alimin; Syamsul Ma’arif Ilyas; Ahmad Tri Muslim HD; Harel Bayu Paizin; Ratnah Umar (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research aims to deconstruct the phenomenon of hyper-independence that massively affects Generation Z within the contemporary digital ecosystem. As digital natives, Generation Z often falls into the trap of extreme self-reliance, which is regarded as a personal achievement but sociologically triggers the disintegration of social capital and societal atomization. The primary issue raised is how technological independence paradoxically creates emotional distance and social apathy toward real-world suffering. Utilizing a qualitative method based on library research and a Social Interpretation (al-tafsir al-ijtima’i) approach, this study positions Surah Al-Ma’un as a theological framework to address this solidarity crisis. The analysis is conducted by creating a dialogue between the Quranic text and digital sociological theories regarding social ties and atomization. The results show that Surah Al-Ma’un offers a radical critique of "religious individualism" by categorizing those who separate prayer rituals from social sensitivity as deniers of the faith. This study finds novelty in the reinterpretation of the term al-ma'un, which in the digital era is no longer limited to simple material aid but has transformed into "collaborative assets" encompassing information literacy, emotional support, and digital resource accessibility for marginalized groups. The research formulates the Inclusive Social Piety model, which integrates three main pillars: spiritual interconnection awareness, digital altruism, and empowering independence. This model functions as a solution to transform the narcissistic "I" paradigm into a collaborative "We" paradigm. In conclusion, the internalization of Al-Ma’un's values acts as a bridge between the personal advancement of Generation Z and their collective responsibility, serving as a basis for character strengthening in Islamic higher education to remain functional and responsive to human problems in the era of disruption.